THE NATURE OF NECROBIOTIC PROCESSES OF LONG-TERM NON-HEALING WOUNDS : // Collection of abstracts of the scientific and practical conference «Current Problems of Surgical Soft Tissue Infections» (2024), Tashkent, October 28 - Umarov, B.Y. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2024)
Among patients with bedsores, cases prevailed (34.5%) of long-term non-healing wounds with the presence of dry necrosis, and to a lesser extent (3.4%), there were cases with the absence of an inflammatory process in the wound. Similar changes were found among patients with neurotrophic ulcers of diabetic foot syndrome, where more than half of the cases (53.6%) in patients with a long-term non-healing wound proceeded against the background of an inflammatory process with the presence of dry tissue necrosis. The absence of any inflammatory phenomenon among patients with this type of long-term non-healing wound was not noted. Among patients with trophic ulcers of the lower extremities due to complications of chronic venous insufficiency, cases of inflammation without tissue necrosis prevailed (48.1%), and the inflammatory process occurred the least (3.7%) against the background of wet necrosis of tissues of long-term non-healing wounds.